Aldose reductase inhibitors attenuate beta-amyloid-induced TNF-alpha production in microlgia via ROS-PKC-mediated NF-kappa B and MAPK pathways - Song, Xiao-Min; Yu, Qian; Dong, Xin; Yang, Hyun Ok; Zeng, Ke-Wu; Li, Jun; Tu, Peng-Fei (ELSEVIER, 2017)
Microglia-mediated neuroinflammation is a key risk factor to the development of Alzheimer' disease (AD). Aldose reductase (AR) has been found to be widely involved in inflammation-related diseases; however, whether aldose reductase inhibitors (ARIs) could be used to treat neuroinflammation is rarely reported. This study aims to evaluate the anti-neuroinflammatory effects of two major ARIs of Sorbinil (Sor) and Zopolrestat (Zol) in beta-amyloid protein (A beta)-induced microglia (BV-2). We find that Sor and Zol significantly inhibit TNF-alpha, IL-1 beta, IL-6 production from microglia in response to All stimulation. Mechanism study showed that Sor and Zol decreased the production of intracellular ROS which resulted in an effective inhibition on the phosphorylation of several protein kinase C (PKC) isoforms including PKC alpha/beta, delta, zeta/lambda and mu. Moreover, Sor and Zol inactivated PCKassociated IKK beta-I kappa B-NF-kappa B and mitogen-activated protein kinase (JNK, p38, ERK) inflammation pathways. In summary, our findings suggest that Sor and Zol could inhibit A beta-induced neuroinflammation by regulating ROS/ PKC-dependent NF-kappa B and MAPK signaling pathways, indicating that ARIs could be promising agents for treating inflammation-related neurodegenerative diseases such as AD.
Keywords: PROTEIN-KINASE-C; ENDOTOXIN-INDUCED UVEITIS; INFLAMMATORY RESPONSE; PHOSPHOLIPASE-C; ACTIVATION; MICROGLIA; EXPRESSION; TRANSCRIPTION; GROWTH; CELLS